Perancangan dan Pembuatan Aplikasi Sistem Informasi Akuntansi Berbasis Web pada Toko Bahan Bangunan UD. Surya Mas - Fendy Haryanto Hansen; Silvia Rostianingsih; Christian Purnama (Jurnal Infra, 2019)
Currently UD. Surya Mas does not have an accounting recording system with good information flow. All recording of transactions is still done manually, causing UD. Surya Mas is vulnerable to loss due to excess stock and stockout costs.Looking at the background of the problem, a structured accounting information system is designed using FIFO stock assumption. The accounting information system was created using PHP and MySql.The results obtained from this application include are master recording, purchase and sale transaction recording, position and mutation report of stocks, debt, accounts receivable, and accounts, as well as basic accounting report such as income statements, balance sheets, journals, and ledgers.